2006
DOI: 10.1007/s10834-006-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Migration Decisions of Dual-earner Families: An Application of Multilevel Modeling

Abstract: A comprehensive framework for guiding analyses of internal migration is lacking. This study contributes to the family migration literature in three important ways. We develop a multilevel theoretical framework emphasizing an integration of individual-, family-, and neighborhood-level effects; introduce multilevel statistical modeling; and explicitly assess how effects of economic-based explanatory variables vary by gender. Our data are from the Panel Study of Income Dynamics (PSID). We find that the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
(41 reference statements)
2
28
1
1
Order By: Relevance
“…Ignoring the combination of education in the household, many papers find that the education of the wife has a small and insignificant effect on family migration once the education of the husband has been controlled for (e.g. Lichter (1982), Nivalainen (2004, Swain and Garasky (2007) and Compton and Pollak (2007, Table 2, column C)).…”
Section: Educational Earnings Potentialmentioning
confidence: 99%
“…Ignoring the combination of education in the household, many papers find that the education of the wife has a small and insignificant effect on family migration once the education of the husband has been controlled for (e.g. Lichter (1982), Nivalainen (2004, Swain and Garasky (2007) and Compton and Pollak (2007, Table 2, column C)).…”
Section: Educational Earnings Potentialmentioning
confidence: 99%
“…13 A significant portion of Indian migrants in the U.S. have a high level of education. This is not surprising-the literature on migration recognizes that the likelihood of migrating increases with educational attainment (see Swain and Garasky 2007). 14 Respondents were allowed to choose multiple destinations for their remittances.…”
Section: Descriptive Statistics and Econometric Estimationmentioning
confidence: 99%
“…The implication is that family migration decisions should have become more consistent with the human capital model over time. And, indeed, more recent studies, with a few important exceptions (Compton and Pollak 2007;Nivalainen 2004;Shauman 2010), have found that the relative effect of the husband's and wife's human capital characteristics in shaping the migration decision has become more symmetrical (Brandén 2013;Eliasson et al forthcoming;Rabe 2011;Smits, Mulder, and Hooimeijer 2003;Smits, Mulder, and Hooimeijer 2004;Swain and Garasky 2007).…”
Section: Introductionmentioning
confidence: 99%